2021
DOI: 10.1016/j.jbc.2021.101369
|View full text |Cite
|
Sign up to set email alerts
|

The GPCR–β-arrestin complex allosterically activates C-Raf by binding its amino terminus

Abstract: G protein–coupled receptors (GPCRs) convert external stimuli into cellular signals through heterotrimeric guanine nucleotide-binding proteins (G-proteins) and β-arrestins (βarrs). In a βarr-dependent signaling pathway, βarrs link GPCRs to various downstream signaling partners, such as the Raf–mitogen-activated protein kinase extracellular signal–regulated kinase–extracellular signal-regulated kinase cascade. Agonist-stimulated GPCR–βarr complexes have been shown to interact with C-Raf and are thought to initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
0
9
1
Order By: Relevance
“…Whether β-arrestin 1 needs to be activated by a phosphorylated receptor for cRaf binding remains controversial. Our results, with HDX-MS and in cell BRET assays, suggest that activated receptors are not required for β-arrestin 1 and cRaf interaction, while a recent study using a GST pull-down assay showed an increased β-arrestin 1 and cRaf interaction when V2Rpp, a phosphorylated C-terminal peptide of the V2 vasopressin receptor, was co-incubated [44,55]. Therefore, further studies are needed to fully understand whether receptor-mediated β-arrestin 1 activation is required for cRaf binding.…”
Section: Structural Mechanism Of Scaffolding Erk1/2 Signaling By β-Ar...contrasting
confidence: 45%
See 1 more Smart Citation
“…Whether β-arrestin 1 needs to be activated by a phosphorylated receptor for cRaf binding remains controversial. Our results, with HDX-MS and in cell BRET assays, suggest that activated receptors are not required for β-arrestin 1 and cRaf interaction, while a recent study using a GST pull-down assay showed an increased β-arrestin 1 and cRaf interaction when V2Rpp, a phosphorylated C-terminal peptide of the V2 vasopressin receptor, was co-incubated [44,55]. Therefore, further studies are needed to fully understand whether receptor-mediated β-arrestin 1 activation is required for cRaf binding.…”
Section: Structural Mechanism Of Scaffolding Erk1/2 Signaling By β-Ar...contrasting
confidence: 45%
“…The observation that β-arrestin 1 interacts with the RBD of cRaf prompted the hypothesis that β-arrestin 1 binding would release the N-terminal domains from the kinase domain, resulting in kinase domain activation (Figure 2D). This hypothesis was confirmed by a recent study in which the kinase activity of cRaf increased upon β-arrestin 1 binding [55]. Whether β-arrestin 1 needs to be activated by a phosphorylated receptor for cRaf binding remains controversial.…”
Section: Structural Mechanism Of Scaffolding Erk1/2 Signaling By β-Ar...mentioning
confidence: 57%
“…The molecular mechanisms underlying β-arrestin scaffolding of the Raf1-MEK1-ERK1/2 cascade (Qu et al, 2021) and likely differences between βarr1 and βarr2 in mediating this process (Perry-Hauser et al, 2022a) are currently the subject of intense investigation. Interestingly, recent data suggest that different GPCR/βarr1 complexes, besides acting as scaffolding proteins, can directly activate, in an allosteric fashion, the protein kinases Src and C-Raf (Pakharukova et al, 2020;Zang et al, 2021).…”
Section: β-Arrestins and Erk1/2 Activationmentioning
confidence: 99%
“…The activation of PAK1 and CHK2 is triggered through the p.S338 site of CRAF via a mechanism independent of its kinase activity [ 197 ]. It was reported that G protein-coupled receptors (GPCRs) activate CRAF through guanine nucleotide-binding G-proteins and the β-arrestins signaling pathway [ 198 ]. Interestingly, β-arrestins specifically bind to the Ras-binding domain of CRAF to balance CRAF activation due to stimuli from G-protein coupled receptors (GPCRs) and the EGFR-RAS signaling cascade.…”
Section: Molecular Regulators Of Crafmentioning
confidence: 99%